Analisis Yuridis Kewajiban Anti Dumping Bagi Sebagian Produk Fatty Alcohol antara Indonesia dan Uni Eropa: Gea Ossita S*, Eduard Awang Maha Putra, Baiq Riska Anggi Safitri - Gea Ossita S; Eduard Awang Maha Putra; Baiq Riska Anggi Safitri (Samudra Publisher, 2023)
This research aims to analyze the case of anti-dumping obligations against fatty alcohol products in the dispute between Indonesia and the European Union. The research method used is normative legal research, using a statutory approach and conceptual approach. The result shows that anti-dumping provisions are regulated internationally in Article VI of GATT 1947. As one of the countries that is part of the World Trade Organization, Indonesia ratified the provisions of GATT-WTO with the issuance of Law Number 7 of 1974 dated November 2, 1994, concerning the ratification of the Agreement on Establishing the World Trade Organization (WTO). The lawsuit filed by Indonesia on the case of the application of anti-dumping obligations applied to some fatty alcohol products from Indonesia was rejected by the international trade dispute settlement panel of the World Trade Organization (WTO), namely the Dispute Settlement Body (DSB) because the European Union could present strong evidence of its reasons for applying anti-dumping obligations to some fatty alcohol products imported by PT Musim Mas, while Indonesia or PT Musim Mas could not prove that the application of anti-dumping obligations carried out by the European Union violated Article 2.4 and Article 3.5 of the anti-dumping agreement, Therefore, Indonesia is proven to have committed dumping in some fatty alcohol products exported to the European Union. Dumping committed by Indonesia is reinforced by the detrimental impact on the domestic industry of similar goods in the European Union in accordance with the provisions of the conditions for dumping in Article 3.5 of the anti-dumping agreement.